(untitled) (Forum Theologicum Sardicense, 2025)
Alexander Georgiev, Development of the Liturgy in the Urban Environment of Constantinople in Preiconoclastic Period. Liturgical forms in Constantinople included imperial and church processions, which played a significant role in the social life of the time. The study of Byzantine urban liturgical processions is varied and extensive, each approach focusing on specific aspects. Key questions include: What was the relationship between the urban landscape, church architecture, and liturgy in the pre-iconoclastic period? Did the visual experience play an important role in the Byzantine stational liturgy within the urban and architectural environment of this period? What was the functional organization of the Byzantine church building in Constantinople, and how were its separate parts arranged according to liturgical planning as a key approach in the study of church architecture? Due to its exceptional value and popularity, the ritual of the liturgical procession was an integral part of Byzantine city life, starting from the legalization of Christianity by Emperor Constantine in 313 AD to the fall of Constantinople in 1453. The Church of St. Sophia occupied a central place in the stational liturgy process from the 5th to the 8th century in Constantinople.